A battle in the hive against the Queen Bee: reaction of female subordinates’ unconcious mind - Baykal, Elif; Surucu, Sevil (Frontiers in Sociology, 2025)
When women in leadership roles act antagonistically toward female subordinates, it’s referred to as the Queen Bee Syndrome. Though it often appears as a top-down dynamic, little is known regarding possible subordinate blowback. With the goal to look into the unconscious reactions of female subordinates performing under female leaders in male-dominated workplaces, this exploratory study utilized a qualitative method. Nine female professionals from an array of industries took part in semi-structured interviews, and MAXQDA was employed to assess the data using both inductive as well as deductive content analysis. Preference for male leaders, perceived difficulties with female managers (such as meticulousness and emotional reactivity), divergent views about female leadership, and the effect of social expectations were the primary four themes that emerged. Findings show that subconscious biases against female superiors may be prevalent among female subordinates, that are comparable to the behaviors typically linked to Queen Bee Syndrome. The “Worker Bee Syndrome,” a reversal dynamic in which workers show bias against female leaders, is introduced in the study. The significance of resolving entrenched biases and workplace gender imbalances is made apparent by these bilateral tensions, which raise doubt on assumptions of unidirectional workplace enmity.